Algorithmic And Mathematical Methods For Solving The Problem Of Calendar Planning Based On Dynamic Functioning Tables - Kabulov Anvar Vasilovich, Kalandarov Ilyos Ibodullayevich, Karimov Anvar Abduvoxidovich (International Journal of Advanced Science and Technology, 2020)
In small-scale and individual production, with frequent changes in the nomenclature, with participation in the production of parts for Assembly of a large number of different sites and workshops, where in turn there are extreme situations, it is not so much impossible to set a single criterion for evaluating the plan, as it is impractical. The planning and management system should be adaptive, with a changing production situation, and be able to adapt to the situation on the site and in the production as a whole. In these conditions, it is necessary to develop new approaches and methods to solve the problems of cladding and management. In this paper, we consider increasing production efficiency using the first method, implemented by managing the organization of production and operational management of the production unit. The most important and complex task in the operational management of a production unit is the task of scheduling. Therefore, the main task of this management problem is the task of calendar planning. The solution of the calendar planning problem is related to the state of a number of internal factors (organizational structures of the placement of workers, equipment, equipment specialization) of the organizational environment of the shop. Therefore, to successfully solve the problems of managing production units, a complex solution of the problems of managing the organization of production and operational management is required.